Glucocorticoids suppress early lung inflammation and impair control of SARS-CoV-2 in non-human primates - Christine E. Nelson; Keith D. Kauffman; Shunsuke Sakai; Taylor Newbolt; Jay Buchanan; Taylor W. Foreman; April M. Walker; Felipe Gómez; Joel D. Fleegle; Richard Herbert; Tom Hill; Sevilay Turan; et al. (PLoS ONE, 2026)
In severe cases of COVID-19, glucocorticoid treatment improves clinical outcomes. However, in non-hospitalized patients, glucocorticoids have limited benefit and may impair viral clearance. Here, we used the rhesus macaque model of acute SARS-CoV-2 infection to investigate the impact of glucocorticoids on host responses and viral control in a setting of mild disease. Rhesus macaques were pre-treated with intravenous methylprednisolone for 5 days prior to SARS-CoV-2 (Delta) infection and maintained on a daily oral prednisolone until necropsy at day 13 post infection. Glucocorticoid (GC) treatment decreased local lung inflammation measured with 18 FDG-PET/CT imaging. GC treated animals also had evidence of elevated SARS-CoV-2 viral titers in the lower airways and pulmonary draining lymph nodes. Glucocorticoid treatment blunted plasmacytoid dendritic cell (pDC), eosinophil, gamma delta T cell and early SARS-CoV-2 specific CD8 T cell responses in the airways. These data reveal the cell types that are directly impacted by immunosuppression with glucocorticoids and provide insights into the mechanism of delayed viral clearance observed with glucocorticoid administration during SARS-CoV-2 infection.